Penjadwalan Flexible Flowshop untuk Penurunan Jumlah Keterlambatan pada Produksi Industrial Glass - Steffen Fang Nyoto; I Gede Agus Widyadana (Jurnal Titra, 2021)
PT. X is a company that has long been engaged in the glass manufacturing business and has several production plants. One of the plants of PT. X., which produces industrial glass have been had delivery lateness around 57% of all orders that have been received during January to May 2021. One of the factors that made lateness in delivery was came from the lack ability from Production Department to fulfil orders because the schedule for each machine did not made regularly. This research wishes to be able to give a scheduling improvement that can lower the rate of delivery lateness. The actual scheduling condition in that plant is done by manually moving the prioritized items with Microsoft Excel program. This research will discuss the proposed Flexible Flowshop scheduling using Microsoft Excel VBA program with the objective function of minimizing the total weighted number of tardy jobs. The results of the proposed scheduling with the Microsoft Excel VBA program have a 25% better solution than the actual method. In addition, this method can shorten the working time of PPIC staff in generating scheduling for each machine.